The relationship of hematological values with Newcastle disease antibody in Thai indigenous chicken: strain Leung Hang Khao - Kongroi, K.; Likitdacharote, B. (International Journal of Agricultural Technology, 2019)
The relationship between hematological values and Newcastle disease immunity of Thai indigenous chicken was studied in strain Leung Hang Khao which attractive to consumers in Thailand. The blood and serum samples were collected from 153 chickens of this strain (mixed sex: male = 70, female = 83) at 4 and 7 months of age raising in free-range condition. Hematological value of the strain Leung Hang Khao at 4 month of age showed the mean corpuscular volume (MCV) in male (126.80±0.51 fl.) was statistically significant (p<0.05) higher than in female (123.30±0.46 fl.). While, the total red blood cell (TRBC), hemoglobin (HGB), hematocrit (HCT), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), total white blood cell count (TWBC), heterophil, lymphocyte, monocyte and H:L ratio were no statistically significant (p>0.05) between sexes at 7 month of age. The average titers were no statistically significant (p>0.05) between sex at 4 month (male: 806.40±97.70 and female: 756.70±87.65) and 7 month (male: 5,372±799.08 and female: 6,561±709.28) of age, respectively. In addition, the hematological values of this strain at 4 month of age was relative to Newcastle disease immunity. The titer was statistically significant (p<0.05) correlation with the hematological value. The titers with the low, medium and high levels of immunity (63.15±23.47, 421.77±28.04 and 1525±131.92, respectively) were negative relationship with lymphocyte (71.00±2.46, 69.79±0.81 and 67.72±1.29 percentages of white blood cell (WBC), respectively) but statistically significant positive (p<0.05) relationship with heterophil (25.17±2.34, 27.76±0.86 and 29.41±1.05 percentages of WBC, respectively). The relationship between the amounts of lymphocyte and heterophil, and Newcastle disease immunity were indicated with the coefficients of phenotypic correlation of -0.17 and 0.18, respectively. From these results showed that, the relationship between hematological values and Newcastle disease immunity could be used as a primary health assessment Newcastle disease index for Thai indigenous chicken strain Leung Hang Khao.